Problems of translation from Egyptian in the correspondence between W. S. Golénischeff and Sir A. H. Gardiner - D. A. Izosimov; P. D. Skorobogatova (Шаги)
The article is devoted to analyzing the correspondence between the British Egyptologist Sir Alan H. Gardiner and the remarkable Russian Orientalist Vladimir Golénischeff. From the start of their lasting exchange of letters both scholars frequently discussed various issues concerning translation from Egyptian into modern languages. During these discussions both Egyptologists shared their opinions on problems of Egyptian syntax and on their own methodology of translations from Egyptian. The following letters shed light on the above-mentioned views and ideas of both well-known scholars. The current article focuses on mainly on the views of Vladimir Golénischeff, who was the most prominent Russian Egyptologist of that time but nevertheless failed to complete and publish his major work, where he would present his own views on various issues of Egyptian philology systematically. However, the correspondence between Alan H. Gardiner and W. S. Golénischeff shows that the Russian Orientalist paid a special attention to Egyptian syntax and to both stylistic and semantic nuances of Egyptian phrases in different contexts. At the same time, Golénischeff was less interested in problems of morphology. Besides, the Russian Orientalist considered the possibilities of contemporary Egyptian philology to be rather limited.